Cellophane Membranes In In Vitro Permeation Studies Using Franz Diffusion Cells: A Review - Nessa Ramawati Jamin; Novia Tri Astuti; Puspa Dwi Pratiwi (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Transdermal drug delivery systems require permeation evaluation to ensure the effectiveness and safety of formulations before clinical application. In vitro permeation testing using the Franz diffusion cell is a widely used method in the early stages of formulation development, as it can describe the drug release and diffusion profile in a controlled manner. One of the synthetic membranes commonly utilized in this system is the cellophane membrane, which is semipermeable, easily obtainable, and provides more reproducible testing conditions compared to biological membranes. This article aims to review the use of cellophane membranes in in vitro permeation studies using Franz diffusion cells and to analyze the parameters reported in the results. The method employed is a literature review conducted through Google Scholar using keywords related to cellophane membranes, Franz diffusion, and in vitro permeation within the period of 2021–2026. The review results indicate that cellophane membranes are used in various dosage forms such as gels, transdermal patches, emulgels, vesicular systems, nanosponges, and solid lipid nanoparticles, with testing conditions generally involving phosphate buffer pH 6.8–7.4 at temperatures of 32–37°C and sampling times up to 24 hours or longer. The most frequently reported parameters include percentage of cumulative drug release, cumulative amount of drug permeated, and flux values. Permeation enhancement is generally influenced by formulation composition, the addition of enhancers, and the type of delivery system used.